Bone marrow mesenchymal stem cells protected post-infarcted myocardium against arrhythmias via reversing potassium channels remodelling - Cai, Benzhi (Blackwell Publishing Ltd, 2014)
Bone marrow mesenchymal stem cells (BMSCs) emerge as a promising approach for treating heart diseases. However, the effects of BMSCs-based therapy on cardiac electrophysiology disorders after myocardial infarction were largely unclear. This study was aimed to investigate whether BMSCs transplantation prevents cardiac arrhythmias and reverses potassium channels remodelling in post-infarcted hearts. Myocardial infarction was established in male SD rats, and BMSCs were then intramyocardially transplanted into the infarcted hearts after 3 days. Cardiac electrophysiological properties in the border zone were evaluated by western blotting and whole-cell patch clamp technique after 2 weeks. We found that BMSCs transplantation ameliorated the increased heart weight index and the impaired LV function. The survival of infarcted rats was also improved after BMSCs transplantation. Importantly, electrical stimulation-induced arrhythmias were less observed in BMSCs-transplanted infarcted rats compared with rats without BMSCs treatment. Furthermore, BMSCs transplantation effectively inhibited the prolongation of action potential duration and the reduction of transient and sustained outward potassium currents in ventricular myocytes in post-infarcted rats. Consistently, BMSCs-transplanted infarcted hearts exhibited the increased expression of K(V)4.2, K(V)4.3, K(V)1.5 and K(V)2.1 proteins when compared to infarcted hearts. Moreover, intracellular free calcium level, calcineurin and nuclear NFATc3 protein expression were shown to be increased in infarcted hearts, which was inhibited by BMSCs transplantation. Collectively, BMSCs transplantation prevented ventricular arrhythmias by reversing cardiac potassium channels remodelling in post-infarcted hearts.